Komparasi Keterampilan Berbicara Siswa Melalui Buku Cerita Pop Up Book Di Kelas IV SD - Wahyuni Nur Rasyidah; Ratna Nila Puspitasari (AL-THIFL : Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The low speaking skills of students are seen from grammatical difficulties, the vocabulary used in storytelling is still few, and fluency is still lacking. There is a factor that makes students less interested in storytelling activities, namely when learning carried out by teachers looks less interesting because it is only one direction. Therefore, in an effort to overcome low speaking skills, the researcher chose the Pop Up Book storybook because it has the advantage of stimulating visuals that are the source of student story material. This research aims to explain the difference in students' speaking skills through the Pop Up Book storybook. This type of research is quantitative with a Pre-experimental design research design with the One Group Pretest-Postest Design model. The population in this study is all grade IV students at SD Negeri 1 Nologaten which is 32 students. Data collection techniques using observation and tests. As for the technical data analysis, the mean formula is used, and standard deviation, normality test, homogeneity test, and independent test. The results of the study showed that 1) The results of speaking skills using the Pop Up Book storybook at the time of Postest the results had reached a minimum standard score or good value of 30 students, while students who had not reached the minimum standard score amounted to 2 students. 2) Based on the results of the t-test test using SPSS version 26, a value of sig. (2-tailed) 0.000 < 0.05 so that there is a significant difference in the speaking skills possessed by students. Thus, it can be concluded that the learning process with Pop Up Book at the Posttest stage has reached the minimum standard and has given good results.